Scrapbook Media Development to Improve IPAS Learning Outcomes - Safira Galuh Yuniarizki; Fitria Dwi Prasetyaningtyas (Postgraduate, University of Mataram, 2025)
The lack of maximum use of learning media due to the limited ability of teachers in creating learning media resulted in students being bored and unfocused, resulting in 17 students out of 27 fourth grade students of SD Bumiayu 01 Pati Regency scoring incomplete on IPAS subjects. This is the background for researchers to create scrapbook learning media as a media tool in learning with the hope of overcoming the problems that occur. Scrapbooks are books with attractive images that are tailored to the subject matter and can be accessed flexibly. The validity test results received a score of 84% by media experts and 93% from material experts. From the results of data analysis obtained, this scrapbook learning media proved to be effective in improving learning outcomes. This statement is evidenced by the acquisition of the paired sample t-test value of 0.00 which means <0.05, meaning that there is a difference in the average pretest and posttest scores. In the N-Gain test getting a value of 0.6291 medium category. So it is concluded that there is an increase in the average IPAS score from 50.8 to 80.5 by students after using the media implemented in learning.